2023
DOI: 10.1093/europace/euad185
|View full text |Cite
|
Sign up to set email alerts
|

EUropean real-world outcomes with Pulsed field ablatiOn in patients with symptomatic atRIAl fibrillation: lessons from the multi-centre EU-PORIA registry

Abstract: Background and Aims Pulsed field ablation (PFA) is a new, non-thermal ablation modality for pulmonary vein isolation (PVI) in patients with atrial fibrillation (AF). The multi-center EU-PORIA (EUropean Real World Outcomes with Pulsed Field AblatiOn in Patients with Symptomatic AtRIAl Fibrillation) registry sought to determine the safety, efficacy, and learning curve characteristics for the pentaspline, multielectrode PFA catheter. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 42 publications
10
58
1
Order By: Relevance
“…Over a median follow‐up of 367 days (IQR: 253–400), overall freedom from AF/AT recurrence after BP was 74.2%, 81.8% for PAF, and 64.8% for persAF. Our findings can be considered in line to what previously published: The recently published EU‐PORIA registry showed a 74% success rate at 1 year in a larger cohort of 1233 patients 15 . However, Reddy et al 5 recorded a higher success rate of 87% at one1 year, but in younger patients compared to our cohort.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Over a median follow‐up of 367 days (IQR: 253–400), overall freedom from AF/AT recurrence after BP was 74.2%, 81.8% for PAF, and 64.8% for persAF. Our findings can be considered in line to what previously published: The recently published EU‐PORIA registry showed a 74% success rate at 1 year in a larger cohort of 1233 patients 15 . However, Reddy et al 5 recorded a higher success rate of 87% at one1 year, but in younger patients compared to our cohort.…”
Section: Discussionsupporting
confidence: 93%
“…The promised preferential tissue ablation with no esophageal lesions or phrenic nerve palsies was confirmed in our study collective. Similar results were reported in the multinational MANIFEST‐PF survey including 1758 patients and the EU‐PORIA registry including 1233 patients 11,15 . Interestingly, the latter study found less cardiac tamponades in operators with single shot device ablation experience 15 .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations